The plankton communities from peat bog pools: structure, temporal variation and environmental factors - Quiroga, María Victoria (2013)
This is the first characterization of the structure and temporal variation of the plankton communities comprising the complete food web in five peat bog pools related to environmental factors over two consecutive ice-free periods in Tierra del Fuego (548S). Remarkably, picophytoplankton was composed solely of eukaryotic cells, surpassing the dominance expectations for these acidic water bodies, whereas testaceans were virtually absent, even as tychoplankters. Abundances of the different planktonic communities were slightly higher than those reported for Northern Hemisphere peat bogs and humic lakes. Mixotrophic nutrition prevailed among nano- and microphytoplankters, a strategy also common in humic lakes. The structures in spring of the planktonic communities were similar. In contrast, in late summer there were differences in the abundance and biomass of the different trophic compartments among small, shallow water bodies and large ones. These seem to be dictated by distinct pool size-driven patterns of water temperature variation. A general shift in the control of heterotrophic flagellates abundance in the pools occurred, changing from bottom-up regulation in spring to top-down control in late summer related to temperature-dependant variations in zooplankton abundance and composition. We hypothesize that changes in the trophic interactions affecting the entire food web occur over the open water period in these aquatic ecosystems, and that these are dictated by pool morphometry and related abiotic features.